Efficacy and Safety of Adapalene Gel and Benzoyl Peroxide Gel in the Treatment of Mild to Moderate Acne Vulgaris: A Single Centre, Double Blind, Parallel Arm Randomized Controlled Trial (Journal of Monno Medical College, 2026)
Background: Acne is a common dermatological disorder of teen age group. There are different modalities of topical and systemic treatments are available to manage this disease.Objective: The purpose of the present study was to evaluate the efficacy and safety of Adapalene 0.1% gel in comparison to Benzoyl Peroxide (BPO) 2.5% gel for the treatment of mild to moderate acne vulgaris.Methodology:  This single centered randomized controlled trial was conducted in the Department of dermatology and venereology Tairunnesa memorial medical college Hospital, Tongi, Gazipur, Bangladesh from October 2023 to April 2024 for a period of six month. A total number of sixty patients of clinically diagnosed acne vulgaris were primarily selected and randomly divided into two equal group (group-A and group-B). Group A was given adapalene 0.1% gel for 12 weeks & Group B was given BPO 2.5% once daily in the evening for same duration. Patients were clinically assessed at baseline and at week 4, 8 and 12. At each visit, the investigator rated, scaling, erythema, dryness, burning, pruritus on a scale ranging from 0 (none) to 3 (severe). Adverse events were evaluated at each visit.Results: A total number of 60 patients were recruited after fulfilling the inclusion and exclusion criteria. Among them predominant age group was 20 to 24 years which were 27 (45.0%). Male: female ratio was 1:2.52. 51(85%) patients had oily skin type and 9(15%) had dry skin type. Adapalene 0.1% gel was significantly more effective than BPO 2.5% gel, with significant differences in total lesion counts observed as early as 4 weeks of treatment. Adverse event frequency and cutaneous tolerability profile was significantly favorable for adapalene gel in the treatment of acne vulgaris.Conclusions: Once daily Adapalene gel provides significantly greater efficacy and safety for the treatment of mild to moderate acne vulgaris compare to Benzoyl Peroxide gel.Journal of Monno Medical College, June, 2025; 11(1) : 54-59